Evaluation of Doctors' Knowledge of Rational Laboratory Use, a Descriptive Study from Turkey - Kilic, Evrim; Tetik, Burcu Kayhan; Kurt, Osman (Duzce Univ, Fac Medicine, 2021)
Objective: The effects of health expenditures on the economy of countries have become more evident in recent years. Especially unnecessary and inappropriate laboratory tests increase both the cost and the workload. In this study, it was aimed to evaluate the level of knowledge of physicians about rational laboratory use and procedure for frequently ordered tests in clinical practice. Methods: This study was planned to be a descriptive study. A questionnaire based on the current circular about 'Rational Laboratory Use' and including sociodemographic data was applied to physicians working at Turgut Ozal Medical Center. Results: The questionnaire was applied to a total of 400 physicians working in internal medicine and surgical branches. The average age of the physicians was 33.01 +/- 5.97 (min = 22, max = 59) years. The question about order period of blood lipids was answered correctly by 3.3% of physicians, HbA1c by 80.8%, Urea / creatinine by 64.5%, and vitamin D and vitamin B12 was answered by 40% of physicians. On the other hand 85.3% of the physicians were not aware of the rational laboratory test ordering procedure and 94% had not received any training on rational laboratory use. Conclusions: It was found that physicians had insufficient knowledge about rational laboratory use and they did not receive any training about the test procedures. In order to reduce health expenditures, more training on this subject should be organized for physicians and awareness should be raised.
Keywords: Rational Laboratory Use; Unnecessary Test Order; Test Order Period